Effect of 5,7-unsaturated sterols on ethanol tolerance in Saccharomyces cerevisiae - Novotný, C; Flieger, M; Panos, J; Karst, F (Biotechnology and applied biochemistry, 1992)
Structural membrane lipids are known to contribute to the high ethanol resistance of Saccharomyces cerevisiae (2, 4, 17). By manipulating the yeast cellular sterol level by changing the carbon-to-nitrogen source ratio in the chemostat growth medium, high delta 5,7-sterol levels were found to increase the resistance of yeast populations to ethanol-induced death. The resistance of the erg2 (delta 8----delta 7-sterol isomerase) mutant to ethanol-induced death was generally comparable with that of the delta 5,7-sterol-synthesizing strain. In contrast, the sensitivity of anaerobic growth to inhibition by ethanol was higher in the erg2 mutant in comparison with the delta 5,7-sterol-synthesizing strains but a high level of those sterols increased the vulnerability of anaerobic growth to ethanol inhibition.
Keywords: mutace; Ethanol; Genes, Fungal; Saccharomyces cerevisiae; steroly; Sterols; mastné kyseliny; geny hub; Anaerobiosis; anaerobióza; Steroid Isomerases; Mutation; ethanol; Fatty Acids; steroidisomerasy